Evidence that metallic proxies are unsuitable for assessing the mechanics of microwear formation and a new theory of the meaning of microwear. Issue 5 (23rd May 2018) - van Casteren, Adam; Lucas, Peter W.; Strait, David S.; Michael, Shaji; Bierwisch, Nick; Schwarzer, Norbert; Al-Fadhalah, Khaled J.; Almusallam, Abdulwahab S.; Thai, Lidia A.; Saji, Sreeja; Shekeban, Ali; Swain, Michael V.
Abstract : Mammalian tooth wear research reveals contrasting patterns seemingly linked to diet: irregularly pitted enamel surfaces, possibly from consuming hard seeds, versus roughly aligned linearly grooved surfaces, associated with eating tough leaves. These patterns are important for assigning diet to fossils, including hominins. However, experiments establishing conditions necessary for such damage challenge this paradigm. Lucas et al . (Lucas et al . 2013 J. R. Soc. Interface 10, 20120923. (doi:10.1098/rsif.2012.0923 )) slid natural objects against enamel, concluding anything less hard than enamel would rub, not abrade, its surface (producing no immediate wear). This category includes all organic plant matter. Particles harder than enamel, with sufficiently angular surfaces, could abrade it immediately, prerequisites that silica/silicate particles alone possess. Xia et al. (Xia, Zheng, Huang, Tian, Chen, Zhou, Ungar, Qian. 2015 Proc. Natl Acad. Sci. USA 112, 10 669–10 672. (doi:10.1073/pnas.1509491112 )) countered with experiments using brass and aluminium balls. Their bulk hardness was lower than enamel, but the latter was abraded. We examined the ball exteriors to address this discrepancy. The aluminium was surfaced by a thin rough oxide layer harder than enamel. Brass surfaces were smoother, but work hardening during manufacture gave them comparable or higher hardness than enamel. We conclude that Xia et al .'s results are actually predicted by the mechanical model of Lucas et al . To explain wear patterns, we present a new model of textural formation, based on particle properties and presence/absence of silica(tes).